Transport properties of concrete containing lithium slag - Amin, Md Tanvir Ehsan; Sarker, Prabir; Shaikh, Faiz (2024)
Lithium Slag (LS), also known as Delithiated Beta Spodumene (DBS), is a by-product of lithium extraction from spodumene ore that contains active silicon dioxide and aluminium oxide making it a potential supplementary cementitious material (SCM) for concrete. This study investigated the transport properties of concrete at 28, 90, and 180 days by incorporating LS as an SCM with cement replacement levels of 20%, 40%, and 60%. The findings reveal that 20% to 40% LS enhanced compressive strength, and reduced permeable voids, water penetration, sorptivity, and porosity, leading to improved transport properties. As LS reacts slowly, 40% LS resulted in 18.34% higher compressive strength at 180 days compared to that of the control mix. Therefore, VPV, water penetration depth, and sorptivity co-efficient of concrete with 40% LS were found 15.96%, 24.79% and 38.46%, respectively, lower than the control mix. In addition, porosity analysis confirmed that with the increase of LS in concrete, porosity decreased over time. Moreover, SEM analysis demonstrated the development of CaCO3 crystals at 40% LS, further reducing porosity. However, beyond 60% cement replacement by LS, a decline in concrete properties was observed due to unreacted LS particles. Therefore, this research underscores the potential use of LS to enhance durability of concrete.